The Critical Target Audience: Communicating Water Conservation Behaviors to Critical Thinking Styles - Laura M. Gorham; Alexa J. Lamm; Joy N. Rumble (Journal of Applied Communications, 2014)
Although water covers approximately 70% of the planet, only a fraction is fresh water, and even less is used as a major source of drinking water. With the continuous increase in the amount of water used in modern standards of living, the quantity of water available is decreasing. The public is beginning to understand water needs to be conserved and they must play a role in water conservation. While previous literature examined how the majority of messages were catered toward the cost-effectiveness of conserving water, this study proposed how using a specific audience attribute could affect behaviors. The purpose of the study was to determine if critical thinking style can be used in the development of future communication strategies to improve water conservation behaviors. The findings of this study provided evidence of a relationship between critical thinking style and the level of engagement in water conservation behaviors. Recommendations suggested targeting the two constructs of critical thinking style, information seekers and engagers, in two different ways. Since the seekers prefer to gather information by seeking the sources themselves, communicators should focus on developing quality information about water conservation and placing it in easily accessible communications channels for the information seeker. On the other hand, a different communications approach should be taken with the engagers, who prefer to learn through their environment. Communicators should focus on communicating to the engager through the environment in word-of-mouth situations using traditional means such as opinion leaders as well as social media.
Keywords: Water conservation; behavior; critical thinking style; and communication